Comparison of three phase shifters for Stirling-type pulse tube cryocoolers operating below 30 K. (April 2018) - Zhu, Haifeng; Jiang, Zhenhua; Liu, Shaoshuai; Jiang, Yanyang; Wu, Yinong
Highlights: Three phase shifters for the second stage of a two-stage SPTC are compared. The cooling performance was investigated theoretically and experimentally. The phase shifting abilities of AWD and MOS are higher than that of ITR. With an AWD phase shifter, a no-load temperature of 18.8 K can be achieved. The efficiency for 1 W@30 K with an AWD is improved by 25% compared to ITR. Abstract: A two-stage Stirling-type pulse tube cryocooler (SPTC) operating below 30 K has been developed for very long baseline interferometry. Three phase shifters namely an inertance tube and reservoir (ITR), an active warm displacer (AWD), and a passive mass-spring oscillator (MSO) have been considered at the second stage cold finger. In order to investigate the effects on the cooling performance, the second stage SPTC with three phase shifters are analyzed theoretically and experimentally. A 1-D numerical model of the two-stage SPTC is built to simulate the cooling performance of the second stage cold finger with the three phase shifters. Using the ITR phase shifter, the maximum COP of the second stage cold finger is 0.014 at 30 K, and a maximum COP of 0.019 can be achieved by the AWD phase shifter, which is also acquired in the second stage cold finger with MSO phase shifter by choosing a proper combination of piston mass and spring constant. Experiments are performed to verify the simulation results. The ITR phase shifter reaches a no-load temperature of 22.08 K, while the AWD phase shifter achieved a no-load temperature of 18.8 K. The MSO phase shifter with a free moving mass spring combination reached a no-load temperature of 20.7 K. The cooling power of 1 W at 30 K requires 93.7 W input PV power of second stage cold finger with ITR phase shifter, but with the AWD and the MSO phase shifters the input PV power is 61 W and 68.7 W, respectively. The SPTC with piston phase shifters (AWD and MSO) could achieve a higher cooling performance than that with ITR phase shifter.